The Effect of Digital Application-Based Nursing Innovation on Patient Satisfaction at Banyumas Hospital in 2025 - Didi Taswidi (CV. Get Press Indonesia, 2026)
The development of digital technology in healthcare has encouraged the implementation of digital application–based nursing innovations to improve service quality and patient satisfaction. The use of digital applications enables real-time documentation, improves data accuracy, and facilitates communication between nurses and patients. However, empirical evidence regarding their impact on patient satisfaction remains limited. This study aimed to analyze the effect of digital application–based nursing innovations on patient satisfaction. This study used a quantitative design with a pre-experimental one-group pretest–posttest approach without a control group. It was conducted at Banyumas Hospital with 80 respondents selected using purposive sampling based on inclusion and exclusion criteria. Data normality was tested using the Shapiro–Wilk test, and bivariate analysis was performed using the paired t-test with a significance level of 0.05. The results showed that the average patient satisfaction score increased from 75.4 ± 7.9 before the intervention to 84.7 ± 6.3 after the intervention. The paired t-test indicated a significant difference (t = 9.12; p < 0.001). In conclusion, digital application–based nursing innovations significantly improve patient satisfaction. Therefore, optimizing digital applications, providing continuous nurse training, and integrating digital systems into standard operating procedures are essential.